DETRIMENTAL EFFECTS OF NATURAL VERTICAL HEAD GRADIENTS ON CHEMICAL AND WATER LEVEL MEASUREMENTS IN OBSERVATION WELLS: IDENTIFICATION AND CONTROL - Elci A.; Flach G.P.; Molz F.J. (My University, 2003)
It is well known that vertical head gradients exist in natural aquifer systems, and borehole flowmeter data have shown that such gradients commonly set up spontaneous vertical flows in monitoring wells, often called ambient flows. What has not been fully appreciated until recently is the serious detrimental effects such flows can have on solute concentration [Ground Water 39 (2001) 853] and hydraulic head measurements in monitoring wells. This communication explores the possibilities of diminishing ambient flows by increasing the hydraulic resistance to vertical flow within monitoring wells and limiting the penetration of such wells. Analyzed also are the surprising effects that vertical gradients may have on the equilibrium water level in a monitoring well. Results are based on collected data, numerical flow simulations, and hydraulic analysis in the near-well vicinity. Raising wellbore hydraulic resistance is of increasing importance and impact in thicker aquifers with higher horizontal hydraulic conductivities (Kh). A systematic analysis of screen penetration revealed that the reduction of ambient flow also depends on aquifer thickness. On a first order basis, the results for homogeneous aquifers may be used to estimate the behavior of a heterogeneous aquifer by computing a power-law average of the heterogeneous Kh(z). Finally, it is evident from the analysis of vertical gradients on well water levels that in the presence of sufficiently high gradients (#h/#z>0.5) it is physically possible for a well screen to be fully submerged below the water table, and yet have an internal water level below the top of the screen. Contrary to common perceptions, water levels in wells spanning the water table deviate significantly from the elevation of the formation water table when the local vertical gradient exceeds about 0.1.
Keywords: AMBIENT FLOW; MONITORING WELL; HYDRAULIC HEAD GRADIENTS; NUMERICAL SIMULATION; WELL SCREENS